ANALISIS MODAL KERJA DALAM MENINGKATKAN PERTUMBUHAN LABA BERSIH PADA PT. PERKEBUNAN NUSANTARA IV MEDAN - Yusri Wulandari; Tri Kartika Yudha (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2019)
Working capital is an important factor for the company because without sufficient capital, the company's operational activities cannot be held. High working capital shows the greater ability of the company to gain profit and will affect the high level of profability as well. The more funds used as working capital are increasing in profit, so it can be said that working capital becomes an element needed by a company because working capital is influential in raising Profit growth. This research was conducted at PT. Plantation Nusantara IV Medan for the period 2013-2017. The purpose of writing this thesis is to know and analyze working capital to increase net profit growth.The data used in this research is the secondary data acquired from the company, and the data analysis method used is a descriptive method and comparative method of methods that attempt to collect data according to the circumstances The truth, presenting and analyding it so that it can give a fairly clear comparison of the objects that are carefully and can then be drawn a conclusion.From the results of the research that the company's working capital has not been optimal in improving net profit growth, based on the results of analysis in the year 2013-2017 showed that the net profit growth was fluctuating or ascending Year 2014 growth is 0.74%, year 2015 dropped to-0.47%, year 2016 back up to 0.40%, and year 2017 fell back to 0.37%. This is due to the fundamental condition of the company has not been effective and efficient in utilizing and using assets, assets and working capital owned by the company.